2007
DOI: 10.1016/j.jalz.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Management of mild to moderate Alzheimer's disease and dementia

Abstract: The authors were charged with making a series of evidence-based recommendations that would provide concrete advice on all aspects of the management of mild to moderate stages of dementia and Alzheimer's disease (AD). The recommendations were primarily targeted to primary care physicians practicing in Canada. The assigned topic area did not include either the assessment of a patient with suspected dementia or the prevention of AD and other dementias. An extensive examination of the available literature was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 273 publications
0
54
0
Order By: Relevance
“…19,20,74 There are several implications of our findings for health service delivery that may improve the health care experience of patients and caregivers throughout these stages. Given that most of the care for patients with dementia can be provided in primary care settings 75 and the limited access to geriatric specialist services, 76 there are several ways that primary care providers may be able to improve the care provided to patients with dementia and their caregivers. First, improving communication and attitudes around dementia were identified as important to patients and caregivers, and primary care providers should be aware of person-centred approaches to care.…”
mentioning
confidence: 99%
“…19,20,74 There are several implications of our findings for health service delivery that may improve the health care experience of patients and caregivers throughout these stages. Given that most of the care for patients with dementia can be provided in primary care settings 75 and the limited access to geriatric specialist services, 76 there are several ways that primary care providers may be able to improve the care provided to patients with dementia and their caregivers. First, improving communication and attitudes around dementia were identified as important to patients and caregivers, and primary care providers should be aware of person-centred approaches to care.…”
mentioning
confidence: 99%
“…During the psychosocial intervention a study clinician provides referrals for caregivers if they are in need of counseling or psychiatric assessment. This psychosocial intervention maintains compliance with the existing standard of care (65,66). …”
Section: Design Of Apathy In Dementia Methylphenidate Trialmentioning
confidence: 92%
“…Although current Canadian consensus guidelines suggest that most patients with dementia can be assessed and managed adequately by their primary care physicians (Hogan et al, 2007), a number of studies have raised concerns about their confidence in diagnosing dementia, the adequacy of their training, and their access to resources in diagnosis and management of dementia. Turner et al (2004) found that one-third of general practitioners surveyed expressed limited confidence in their diagnostic skills and two-thirds lacked confidence in management of behavior and other problems in dementia.…”
Section: Early Diagnosis and Treatmentmentioning
confidence: 99%